Revealing Structural Brain-Cognition Relationships in Children: A Comparison of Morphometric Similarity and INverse Divergence Networks - Shuning Han; Hao Jia; Gemma Vilaseca; Núria Vilaró; Feng Duan; Zhe Sun; Cesar F. Caiafa; Jordi Solé-Casals (Neuroinformatics, 2026)
The study of structural brain networks (SBNs) offers critical insights into brain-cognition relationships. However, a comprehensive comparison of these methods in terms of their topological properties, cognitive relevance, and sensitivity to connection density remains lacking. This study compares two types of individual-level SBNs–morphometric similarity networks (MSNs) and morphometric inverse divergence (MIND) networks–by analyzing their associations with cognitive performance using sMRI data from 29 male children. Group- and individual-level analyses were conducted to evaluate differences in hemispheric connectivity, topological features, and their correlations with cognitive performance across different connection densities. In our analyses, a connection density of $$p=0.05\sim 0.15$$ appeared optimal for stabilizing network properties and maximizing cognitive correlations in both MSN and MIND. Moreover, advanced network segregation and integration metrics (such as local efficiency and node versatility, along with their global summaries) demonstrated greater sensitivity to cognitive performance. However, MSNs appeared to provide a more reliable framework, demonstrating more stable associations across connection densities in topological and hemispheric dimensions. Specifically, higher cognitive performance may be linked to stronger left intra-hemispheric connectivity, weaker inter-hemispheric connectivity, and more modular network organization–consistent with established theories of hemispheric specialization and efficient modularity. In contrast, MIND networks exhibit reduced effectiveness and stability across metrics and densities in our data. These preliminary insights enhance our understanding of brain-cognition relationships and provide practical guidelines for parameter selection and metric identification in network-based cognitive analyses.

Can Hematological Biomarkers Indicate Diagnoses and Prognosis in Stranded Harbor Seals ( Phoca vitulina )? - Bradley C. England; Joanna L. Kershaw; Ana Rubio‐Garcia; Anna Salazar‐Casals; Debbie J. F. Russell (Marine Mammal Science, 2026)
Wildlife health assessments offer critical insights in applied ecological research, but their interpretation is often limited by missing complementary data. There is heightened need for such data for European harbor seals ( Phoca vitulina vitulina ) given their recent population decline. We investigated trends in and hematological markers of health and survival of pre‐ and post‐ weaned harbor seal pups using a 10‐year rehabilitation database ( n = 2428), and established hematological reference ranges from clinically healthy pups at release (age 3–12 months; n = 260). Hematological parameters at admission were related to pup age class and diagnoses. Specifically, values for parasitic pneumonia—the predominant diagnosis at admission for post‐weaned pups—fell outside reference ranges for some parameters. Both body mass and hematological parameters at admission were related to the probability of surviving to release. Parameters associated with survival differed with age class but included those closely related to immune function, parasitic burden, anemia, and dehydration. Trends in admission numbers and body mass were mostly driven by changes in stranding protocols; however, there was an indication of emerging trends associated with population decline. These findings provide hematological markers to assess health and survival of both stranded and free‐living harbor seal pups.

Surgical Process Modeling of Workflow and Performance in Image-Guided Bronchoscopy - Tatiana A. Rypinski; Roberto F. Casal; Parvathy S. Pillai; Anshuj Deva; Bhavin Soni; Owais Sarwar; Aaron C. Milhorn; Aaron K. Jones; Gouthami Chintalapani; Gerhard Kleinszig; David E. Ost; Horiana B. Grosu; et al. (Annals of Biomedical Engineering, 2025)

European Atlantic deciduous forests are more resilient to fires than Pinus and Eucalyptus plantations - Óscar Cruz; Sheila F. Riveiro; Juan García-Duro; Mercedes Casal; Otilia Reyes (Forest Ecology and Management, 2024)

Angler’s preferences, perceptions and practices regarding non-native freshwater fish - F. Banha; J. Gago; D. Margalejo; J. Feijão; F. Casals; P. M. Anastácio; F. Ribeiro (Reviews in Fish Biology and Fisheries, 2024)
It is globally recognized that freshwater anglers can have a decisive role in promoting fish introductions. The aim of this study was to analyze freshwater anglers’ actions and perceptions regarding fish introductions, comparing two distinct situations, one with recently arrived non-natives fishes and another with older fish introductions, using the Iberian Peninsula as a case study. To achieve this goal, a bilingual survey was implemented on-line in Portugal and Spain and in person (direct inquiries) in two Iberian regions: Lower Ebro (older fish introductions) in Spain; and Lower Tagus (recent fish introductions) in Portugal. Results showed spatial differences in perceptions and actions, namely about the target species, awareness of the impact of non-native fishes, fish introductions reported and proportion of anglers that wanted new fish species. In the Ebro river there is a high percentage of foreign anglers, higher awareness of fish introduction impact and lower introduction rates reported than in the Tagus river. However, popularity of non-native species like European catfish, was higher in the Ebro. In general, although risk behaviors such as use of fish as life bait was of low prevalence for both countries (approx. 5%), it corresponds to large numbers of fish being introduced. Our conservative estimates revealed 273,600 events of bait discharge per year. Regarding the intentional introductions, we estimated a total of 140,000 intentional introduction (illegal) events per year. These findings may help to improve monitoring, awareness and fisheries management programs led by governmental agencies. Graphical abstract

Performance of length-based assessment in predicting small-scale multispecies fishery sustainability - Wendell Medeiros-Leal; Régis Santos; Ualerson I. Peixoto; Morgan Casal-Ribeiro; Ana Novoa-Pabon; Michael F. Sigler; Mário Pinho (Reviews in Fish Biology and Fisheries, 2023)
Small-scale fisheries play a critical role in food security and contribute to nearly half of reported global fish catches. However, the status of most small-scale fisheries stocks is still poor. In data-limited situations, length-based methods have been widely applied to estimate reference points and to understand stock status. This study applied three different length-based assessment methods (length-based indicators—LBI, length-based spawning potential ratio—LBSPR, and the length-based Bayesian biomass approach—LBB) to predict fisheries stock sustainability in the Azores. Overall, the three methods showed robustness for 15 out of 18 stocks assessed and agreed on their exploitation status. The results showed that 45% of the Azorean stocks were classified as sustainable stocks , 33% possible rebuilding/overfished and 22% overfishing/overfished stock status. Sensitivity analysis showed that biases on the source of initial life-history parameters, especially the asymptotic length (L∞) and the ratio of natural mortality and growth coefficient (M/k), have a stronger influence on the reference points of conservation of mature individuals (LBI), spawning potential ratio and fishing mortality (LBSPR) and the biomass relative to the maximum sustainable yield (LBB). Furthermore, sensitivity analysis indicated that, among the three methods, LBI is more robust. Our findings provide some management recommendations such as (1) catches and effort should be reduced; (2) minimum landing size should be increased; (3) minimum hook size should be increased, to be applied mainly for those stocks classified as possible rebuilding/overfished and overfishing/overfished stock status. Graphical abstract

Towards Improving Motor Imagery Brain–Computer Interface Using Multimodal Speech Imagery - Jigang Tong; Zhengxing Xing; Xiaoying Wei; Chao Yue; Enzeng Dong; Shengzhi Du; Zhe Sun; Jordi Solé-Casals; Cesar F. Caiafa (Journal of Medical and Biological Engineering, 2023)
Purpose The brain–computer interface (BCI) based on motor imagery (MI) has attracted extensive interest due to its spontaneity and convenience. However, the traditional MI paradigm is limited by weak features in evoked EEG signal, which often leads to lower classification performance. Methods In this paper, a novel paradigm is proposed to improve the BCI performance, by the speech imaginary combined with silent reading (SR) and writing imagery (WI), instead of imagining the body movements. In this multimodal (imaginary voices and movements) paradigm, the subjects silently read Chinese Pinyin (pronunciation) and imaginarily write the Chinese characters, according to a cue. Results Eight subjects participated in binary classification tasks, by carrying out the traditional MI and the proposed paradigm in different experiments for comparison. 77.03% average classification accuracy was obtained by the new paradigm versus 68.96% by the traditional paradigm. Conclusion The results of experiments show that the proposed paradigm evokes stronger features, which benefits the classification. This work opens a new view on evoking stronger EEG features by multimodal activities/stimuli using specific paradigms for BCI.

3-aryl-indolinones derivatives as antiplasmodial agents: synthesis, biological activity and computational analysis - Ayelen Luczywo; Lucía G. González; Anna C. C. Aguiar; Juliana Oliveira de Souza; Guilherme E. Souza; Glaucius Oliva; Luis F. Aguilar; Juan J. Casal; Rafael V. C. Guido; Silvia E. Asís; Marco Mellado (Natural Product Research, 2022)

Effects of irradiance of red and blue:red LEDs on Scenedesmus obliquus M2-1 optimization of biomass and high added-value compounds - Fernando Pagels; Helena M. Amaro; Tânia G. Tavares; Susana Casal; F. Xavier Malcata; Isabel Sousa-Pinto; A. Catarina Guedes (Journal of Applied Phycology, 2021)

The carboxylic acid transporters Jen1 and Jen2 affect the architecture and fluconazole susceptibility of Candida albicans biofilm in the presence of lactate - Rosana Alves; Sandra Mota; Sónia Silva; Célia F. Rodrigues; Alistair J. P. Brown; Mariana Henriques; Margarida Casal; Sandra Paiva (Biofouling, 2017)

Ventilator-associated pneumonia by methicillin-susceptible Staphylococcus aureus: do minimum inhibitory concentrations to vancomycin and daptomycin matter? - J. Ruiz-Ramos; P. Vidal-Cortés; A. Díaz-Lamas; R. Reig-Valero; F. Roche-Campo; M. Del Valle-Ortiz; X. Nuvials-Casals; M. Ortiz-Piquer; D. Andaluz-Ojeda; L. Tamayo-Lomas; M. A. Blasco-Navalpotro; M. Rodriguez-Aguirregabiria; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Life cycle inference and phylogeny of Ortholinea labracis n. sp. (Myxosporea: Ortholineidae), a parasite of the European seabass Dicentrarchus labrax (Teleostei: Moronidae), in a Portuguese fish farm - L F Rangel; S Rocha; G Casal; R Castro; R Severino; C Azevedo; F Cavaleiro; M J Santos (Journal of Fish Diseases, 2017)
Ortholinea labracis n. sp. is described and its life cycle is inferred from a Southern Portuguese fish farm, with basis on microscopic and molecular procedures. This myxosporean parasite infects the urinary bladder of the European seabass Dicentrarchus labrax and the intestinal epithelium of a marine oligochaete of the genus Tectidrilus . Myxospores subspherical in valvular view and ellipsoidal in sutural view measuring 7.6 ± 0.3 (6.8–8.7) μm in length, 7.2 ± 0.2 (6.7–7.7) μm in width and 6.5 ± 0.4 (5.8–7.7) μm in thickness. Two polar capsules, 3.0 ± 0.2 (2.6–3.4) μm long and 2.4 ± 0.1 (2.0–2.9) μm wide, located at the same level, but with divergent orientation and opening to opposite sides of the suture line. Sequencing of the SSU rRNA gene revealed a similarity of 100% between the analysed myxospores and triactinomyxon actinospores. The phylogenetic setting of O. labracis n. sp. shows subgrouping in correlation with tissue tropism, but identifies this parasite as another exception to the main division of Myxosporea into the main freshwater and marine lineages.

Determinants of grassland primary production in seasonally-dry silvopastoral systems in Central America - G. M. Rusch; P. C. Zapata; F. Casanoves; P. Casals; M. Ibrahim; F. DeClerck (Agroforestry Systems, 2014)

In vitro susceptibility of high virulence microorganisms isolated in heart valve banking - R. Villalba; F. Solis; G. Fornés; A. Jimenez; M. Eisman; Ana I. González; M. J. Linares; M. Casal; J. L. Gómez Villagrán (Cell and Tissue Banking, 2012)

Genetic basis of long shelf life and variability into Penjar tomato - J. Casals; L. Pascual; J. Cañizares; J. Cebolla-Cornejo; F. Casañas; F. Nuez (Genetic Resources and Crop Evolution, 2012)

Life‐history traits of the stone loach Barbatula barbatula - D. Vinyoles; A. De Sostoa; C. Franch; A. Maceda‐Veiga; F. Casals; N. Caiola (Journal of Fish Biology, 2010)
The life‐history tactics of the stone loach Barbatula barbatula were studied in a Mediterranean‐type climate stream (Matarranya River) located in the Ebro River basin (north‐east Spain). Maximum observed ages were 2+ years in both sexes (1% of individuals), although only 0+ and 1+ year age groups were well represented. It is the lowest longevity reported for this species in its entire distribution. The seasonal growth period started in June and continued until November, but the pattern observed was different to northern populations. Barbatula barbatula in the Matarranya River was a multiple spawner, releasing small batches of oocytes between April and June. The fecundity of females was higher and the size of oocytes smaller in 1984 than in 1985. The relative fecundity (number of ripening and ripe oocytes g −1 of fish) was lower than in northern European populations. The role of the particular environmental conditions of a Mediterranean stream was discussed in relation to the life‐history tactics of B. barbatula .

Assessing perturbation of river fish communities in the Iberian Ecoregion - T. FERREIRA; N. CAIOLA; F. CASALS; J. M. OLIVEIRA; A. DE SOSTOA (Fisheries Management and Ecology, 2007)
A spatially based approach was used to analyse the response of fish‐based metrics to human impacts in the Iberian Peninsula. A fish‐based typology was established that distinguished one salmonid type (fish assemblages dominated by Salmo trutta fario L.), two mixed types ( S. trutta fario associated with different cyprinids) and six cyprinid types (dominated by different species of barbel [ Barbus spp.], nase [ Chondrostoma spp.] or chub [ Leuciscus spp.]). These types broadly correspond to different forms of ecosystem functioning, ranging from the cold, northern and high altitude sections to warmwater, lowland and southern sections. Twenty metrics were identified that responded to disturbance – four to 14 per fish type. The highest correlations were −0.795 for abundance of Squalius sp. and segment (localised) disturbance and 0.754 for abundance of limnophilic specimens and water quality disturbance. Disturbance of segment, habitat and hydrological regime yielded more metric responses in western Iberian fish types, while that of habitat and water quality gave more in north‐eastern Iberian fish types. Global (catchment scale) disturbance generally gave more responsive metrics and higher correlations than partial disturbances. All guilds were represented and a number of metrics were responsive across fish types – namely native species, alien abundance, water column (natives), eurytopic and invertivorous (natives). However, several metrics were only reactive in one or a few types, such as benthic and S. trutta fario in north‐western mixed fish type. Different trends in metric reaction occurred for total abundance in north‐western mixed fish type, and for eurytopic and phytophilic (natives) in the north‐eastern fish types.

Ecological traits of fish assemblages from Mediterranean Europe and their responses to human disturbance - T. FERREIRA; J. OLIVEIRA; N. CAIOLA; A. DE SOSTOA; F. CASALS; R. CORTES; A. ECONOMOU; S. ZOGARIS; D. GARCIA‐JALON; M. ILHÉU; F. MARTINEZ‐CAPEL; D. PONT; et al. (Fisheries Management and Ecology, 2007)
Mediterranean river systems are characterised by more diverse fish assemblages and regional ecological processes compared with the rest of Europe. A data set from Mediterranean France, Iberia and Greece (∼2000 sites) was used to describe the characteristics of fish assemblages, explore their responses to anthropogenic disturbance and analyse the implications for river quality assessment. There was a southwards decline in species richness per site, but endemicity and proportion of alien species increased. Sites in the eastern Mediterranean had higher endemicity, lower site richness and lower number of alien species than sites in western Mediterranean Europe. Assemblage composition differed between Mediterranean sub‐regions, but was dominated by three major fish types: a salmonid fish type common throughout the study area and two cyprinid‐dominated fish types (in some sub‐regions, Salmo trutta L. is present but not numerically dominant), corresponding to a gradient in hydrological and temperature regimes. Metric responses to perturbation were compared with those found at the European (larger scale) and basin (smaller scale) levels. Overall metric response was weaker in this Mediterranean application. The best responses to human pressure were usually obtained with abundance‐based metrics and included the contribution of naturalised alien species. Some widespread alien species contributed to the response to anthropogenic alteration (notably Cyprinus carpio L. and Lepomis gibbosus (L.)).

Molecular basis of 3-hydroxy-3-methylglutaric aciduria - J. Pie; N. Casals; B. Puisac; F. G. Hegardt (Journal of Physiology and Biochemistry, 2003)

Genetic basis of mitochondrial HMG-CoA synthase deficiency - Rosa Aledo; Johannes Zschocke; Juan Pié; Cecilia Mir; Sonja Fiesel; Ertan Mayatepek; Georg F. Hoffmann; Núria Casals; Fausto G. Hegardt (Human Genetics, 2001)

Characterization of a novel 21-kb deletion, CFTRdele2,3(21 kb), in the CFTR gene: a cystic fibrosis mutation of Slavic origin common in Central and East Europe - T. Dörk; M. Macek Jr; F. Mekus; B. Tümmler; J. Tzountzouris; T. Casals; A. Krebsová; M. Koudová; I. Sakmaryová; M. Macek Sr; V. Vávrová; D. Zemková; et al. (Human Genetics, 2000)

A new approach for identifying non-pathogenic mutations. An analysis of the cystic fibrosis transmembrane regulator gene in normal individuals - C. Bombieri; S. Giorgi; S. Carles; R. de Cid; F. Belpinati; C. Tandoi; N. Pallares-Ruiz; C. Lazaro; B.M. Ciminelli; M.-C. Romey; T. Casals; F. Pompei; et al. (Human Genetics, 2000)

A new approach for identifying non-pathogenic mutations. An analysis of the cystic fibrosis transmembrane regulator gene in normal individuals - C. Bombieri; S. Giorgi; S. Carles; R. de Cid; F. Belpinati; C. Tandoi; N. Pallares-Ruiz; C. Lazaro; B.M. Ciminelli; M.-C. Romey; T. Casals; F. Pompei; et al. (Human Genetics, 2000)

Complex allele [-102T>A+S549R(T>G)] is associated with milder forms of cystic fibrosis than allele S549R(T>G) alone - M.-C. Romey; C. Guittard; J.-P. Chazalette; P. Frossard; K.P. Dawson; M.A. Patton; T. Casals; T. Bazarbachi; E. Girodon; G. Rault; D. Bozon; F. Seguret; et al. (Human Genetics, 1999)

Complex allele [-102T>A+S549R(T>G)] is associated with milder forms of cystic fibrosis than allele S549R(T>G) alone - M.-C. Romey; C. Guittard; J.-P. Chazalette; P. Frossard; K.P. Dawson; M.A. Patton; T. Casals; T. Bazarbachi; E. Girodon; G. Rault; D. Bozon; F. Seguret; et al. (Human Genetics, 1999)